2012
DOI: 10.1152/ajprenal.00675.2011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insulin on Na and K transporters in the rat CCD

Abstract: We tested the effects of insulin (2 nM, 30-60 min) on principal cells of isolated split-open rat cortical collecting ducts (CCD) using whole-cell current measurements. Insulin addition to the superfusate of the tubules enhanced Na pump (ouabain-sensitive) current from 18 ± 3 to 31 ± 3 pA/cell in control and from 74 ± 9 to 126 ± 11 pA/cell in high K-fed animals. It also more than doubled ROMK (tertiapin-Q-sensitive) K(+) currents in control CCD from 320 ± 40 to 700 ± 80 pA/cell, although it did not affect this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 35 publications
(58 reference statements)
0
33
0
Order By: Relevance
“…A recent small RCT in children ≤12 years old showed that low dose (0.05 unit/kg/h) was comparable to standard dose (0.1 U/kg/h) with respect to rate of blood glucose decrease and resolution of acidosis; however, there was also no evidence that the higher dose (0.1 U/kg/h) is harmful Insulin has an aldosterone‐like effect leading to increased urinary potassium excretion . High doses administered intravenously for a prolonged period of time may contribute to a decrease in serum potassium concentration due to increased urinary potassium excretion despite potassium administration. Time on IV insulin infusion and dose of insulin should be minimized to avoid severe hypokalemia …”
Section: Clinical and Biochemical Monitoringmentioning
confidence: 99%
“…A recent small RCT in children ≤12 years old showed that low dose (0.05 unit/kg/h) was comparable to standard dose (0.1 U/kg/h) with respect to rate of blood glucose decrease and resolution of acidosis; however, there was also no evidence that the higher dose (0.1 U/kg/h) is harmful Insulin has an aldosterone‐like effect leading to increased urinary potassium excretion . High doses administered intravenously for a prolonged period of time may contribute to a decrease in serum potassium concentration due to increased urinary potassium excretion despite potassium administration. Time on IV insulin infusion and dose of insulin should be minimized to avoid severe hypokalemia …”
Section: Clinical and Biochemical Monitoringmentioning
confidence: 99%
“…In patients with acromegaly, augmented circulating IGF-1 levels result in antinatriuresis and hypertension, which can be corrected with ENaC inhibitor amiloride (14,15). In contrast, the effects of insulin are very dependent on plasma glucose and K ϩ levels and often do not lead to salt retention and elevation in blood pressure (5,20). Furthermore, IGF-1 reduces renal potassium excretion (6), whereas insulin can promote kaliuresis (5), particularly when plasma K ϩ levels are exogenously clamped (9,36).…”
mentioning
confidence: 99%
“…However, it is also possible that it is another collecting duct principal cell factor, e.g., reduced Na-K-ATPase activity, that affects baseline BP in these mice (23). It is reasonable to predict that insulin acts as a tonic facilitator of sodium reabsorption via ENaC, especially after meals, to allow for efficient retrieval of filtered sodium.…”
Section: Discussionmentioning
confidence: 99%
“…We've also shown that insulin results in antinatriuresis in mice, which was inhibitable by the ENaC antagonist, benzamil (56). However, another recent study (23) did not show activation of ENaC by physiological levels of insulin in the split-open rat cortical collecting duct tubule, but that Na-K-ATPase and K ϩ channels were activated. This might provide a driving force for increased sodium reabsorption in this tubule segment.…”
mentioning
confidence: 87%